Ancient genomes reveal the genetic structure and population interaction in the Central Plains of China during the Eastern Zhou Period - Wu, Xiyan; Liu, Pengxiang; Yan, Fei; Jin, RongPeng; Zhong, Canshuo; Wang, Lin; Chen, Ke; Yang, Fan; Nie, Linyi; Liang, Jinteng; Zhou, Yawei; Ding, Baoxu (Frontiers in Microbiology, 2025)
The Eastern Zhou period (770–256 BCE) was a transformative era in ancient China, marked by intensified social stratification, frequent warfare, and increased population movements. The Western Guo State, as an important vassal state during the Western Zhou period, migrated eastward with King Ping of Zhou and was eventually conquered by the Jin State. Due to limited genomic data, the genetic history of the Guo State population remains unclear. The Shangshihe cemetery, located in Yima City, Henan Province, is hypothesized to be associated with the Guo State and provides an opportunity to understand the genetic dynamics of this period. In our study, we successfully obtained 13 ancient genomes from the Shangshihe cemetery. Our findings suggest notable maternal and paternal genetic diversity within the Shangshihe population, although this observation is limited by the small sample size. Population genomic analysis shows that the Shangshihe individuals are predominantly of Yellow River Basin-related ancestry, with minor contributions from Southern East Asian-related and Eurasian Steppe-related sources. This genetic profile reflects extensive interactions between the Central Plains and surrounding populations during the Eastern Zhou period. Additionally, while distinct Y-chromosome haplogroups were observed among individuals with different burial orientations, autosomal analysis did not detect significant genetic differentiation, indicating overall genetic homogeneity within the population. These results not only elucidate the genetic characteristics of the Guo State population but also provide a new genetic perspective on the population dynamics and cultural exchanges in the Central Plains during the Eastern Zhou period.